Hybrid effect of Sm and B4C on grain size stability and hardness of nanocrystalline CoCrFeNi high entropy alloy after isothermal annealing - Tasdemir, Esma; Koc, Recep C.; Batibay, Ahmet B.; Kotan, Hasan (Elsevier Science Sa, 2025)
In this study, a hybrid effect of Sm and B4C additions is explored to enhance the thermal stability of mechanically alloyed nanocrystalline CoCrFeNi HEA after exposures to long-term annealing at 700 degrees C and 900 degrees C. The structural and microstructural investigations were carried out using X-ray diffraction (XRD), focused ion beam microscopy (FIB), and scanning transmission electron microscopy (STEM) with energy dispersive spectroscopy (EDS). The results revealed that 7 nm grain size of as-milled CoCrFeNi HEA coarsened to 247.38 f 69 nm after 1 h of annealing at 900 degrees C. However, the hybrid addition of Sm and B4C significantly retarded grain growth, reducing the average grain size to 98.74 f 47 nm after 24 h of annealing at the same temperature. The resistance to grain growth is attributed to Sm and B4C additions and the formation of Sm-based oxide phases during annealing. The influence of microstructures on hardness was utilized to examine the mechanical changes as a function of annealing temperature and annealing time. Accordingly, the hardness of CoCrFeNi, measured as 517.8 f 25 HV after mechanical alloying, decreased significantly to 321 f 10 HV and 277 f 13 HV after 1 and 24 h of annealing at 900 degrees C, respectively. In contrast, the hybrid HEA maintained a hardness of 439.5 f 10 HV even after 24 h of annealing at 900 degrees C. Compared to the individual additions of Sm and B4C, the hybrid addition also proved more effective in preserving hardness at elevated temperatures over time. Overall, exploring the hybrid effect of alloying and second-phase addition provides a promising strategy for improving the grain size stability and the mechanical properties of nanocrystalline CoCrFeNi HEAs.
Keywords: High entropy alloys; Nanocrystalline; Grain growth; Hybrid effect; Thermal stability; Isothermal annealing; Sm